Pengaruh Pemberian Asi Predominan, Status Gizi, Tipe Pola Asuh Terhadap IQ Anak Usia 5-6 Tahun - Yunarsih Yunarsih (coba, 2013)
The purpose of this study was to determine the effect of predominant breastfeeding, nutritional status, and type of parenting style on the level of intelligence (IQ) of children aged 5-6 years in kindergarten Sugihwaras Prambon Nganjuk Earth. The study design was an observational analytic. The populations are mothers of children aged 5-6 years in kindergarten Earth II Prambon Nganjuk Sugihwaras as 48 person. The sample in this study was taken by random sampling technique as 46 person. The results of multivariate analysis showed that the variables simultaneously predominant breastfeeding, nutritional status and type of parenting style affects the level of intelligence (IQ) in which parenting variables have the greatest influence with the value of b = 0.462, followed by predominantly breast-feeding variable with a value of b = 0.426 and the smallest effect nutritional status is a variable with a value of b = 0.220 and a value of p= 0,000. Key words: Predominant breastfeeding, nutritional status, parenting, IQ